Factors Associated with Pre-Marital Sexual Behavior Among Adolescents in Bima, West Nusa Tenggara: Theory of Planned Behavior - Mulya Tarmidi; Argyo Demartoto; Eti Poncorini Pamungkasari (Journal of Health Promotion and Behavior, 2018)
Background: Adolescent reproductive health is a major global challenge. Studies have reported around 16 million women 15